1998
DOI: 10.1093/bja/81.5.757
|View full text |Cite
|
Sign up to set email alerts
|

Neostigmine with glycopyrrolate does not increase the incidence or severity of postoperative nausea and vomiting in outpatients undergoing gynaecological laparoscopy

Abstract: We studied 100 healthy women undergoing outpatient gynaecological laparoscopy in a randomized, double-blind and placebo-controlled study to evaluate the effect of neostigmine on postoperative nausea and vomiting (PONV). After induction of anaesthesia with propofol, anaesthesia was maintained with sevoflurane and 66% nitrous oxide in oxygen. Mivacurium was used for neuromuscular block. At the end of anaesthesia, neostigmine 2.0 mg and glycopyrrolate 0.4 mg, or saline, was given i.v. The incidence of PONV was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 15 publications
1
21
1
Order By: Relevance
“…21 It has been reported that neuromuscular block antagonism with 2 mg neostigmine in laparoscopic gynecological operations did not cause an increase in the incidence of PONV. 22 The noticeable point in these two studies is the amount of neostigmine used. It has been determined that use of neostigmine in doses above 2.5 mg increases the risk of PONV.…”
Section: Discussionmentioning
confidence: 99%
“…21 It has been reported that neuromuscular block antagonism with 2 mg neostigmine in laparoscopic gynecological operations did not cause an increase in the incidence of PONV. 22 The noticeable point in these two studies is the amount of neostigmine used. It has been determined that use of neostigmine in doses above 2.5 mg increases the risk of PONV.…”
Section: Discussionmentioning
confidence: 99%
“…Because opioids are a potent cause of PONV, the concomitant use of NSAIDs and opioids helps to better control postoperative pain, while decreasing opioid-related side effects. The routine use of neostigmine to reverse residual neuromuscular block has been reported to increase the incidence of PONV compared with spontaneous recovery from mivacurium [43]; however, others have failed to confirm an adverse effect of neostigmine in a similar study [96].…”
Section: Anesthetic Techniquementioning
confidence: 99%
“…8 Large doses of acetylcholinesterase inhibitors may cause nausea and vomiting. [9][10][11][12][13][14][15] Prevention of these muscarinic adverse effects requires coadministration of an anticholinergic agent such as atropine and, more commonly, the quaternary ammonium compound glycopyrrolate. The administration of an anticholinergic agent also carries the risk of adverse effects, such as cardiac dysrhythmia, 16 excessive tachycardia, 17 and xerostomia.…”
Section: Nondepolarizing Neuromuscular Junction Blocker Reversalmentioning
confidence: 99%